Pengaruh Green Accounting, Kinerja Lingkungan, Ukuran Perusahaan dan Likuiditas terhadap Profitabilitas: - Fitrifatun, Nailil; Meirini, Dianita (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research is useful for identifying the effect of implementing green accounting, environmental performance, firm size and liquidity on company profitability in mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The method used in this study is a quantitative method with using purposive sampling as a sampling technique, according to predetermined criteria. So that a sample of 24 mining sector companies were obtained which were listed on the IDX from 2018 to 2022. This study used secondary data obtained from the company's annual report. The variables used in this study are independent variables, namely green accounting (X1), environmental performance (X2), firm size (X3), liquidity (X4), and the dependent variable, namely profitability (Y). The data analysis technique in this study was a panel data regression test using Eviews 12 software. Partially (T test) it was found that green accounting has a significant negative effect on profitability, but environmental performance, firm size, and liquidity have a significant positive effect on company profitability. Simultaneously (F test) the results show that green accounting, environmental performance, firm size and liquidity have a significant effect on company profitability. Keywords: Environmental performance; firm size; green accounting; liquidity; profitability.